Fluvial Organic Carbon Composition Regulated by Seasonal Variability in Lowland River Migration and Water Discharge. Issue 24 (22nd December 2021) - Golombek, Nina Y.; Scheingross, Joel S.; Repasch, Marisa N.; Hovius, Niels; Menges, Johanna; Sachse, Dirk; Lupker, Maarten; Eglinton, Timothy I.; Haghipour, Negar; Poulson, Simon R.; Gröcke, Darren R.; Latosinski, Francisco G.; et al.
Abstract: Identifying drivers of seasonal variations in fluvial particulate organic carbon (POC) composition can aid sediment provenance and biogeochemical cycling studies. We evaluate seasonal changes in POC composition in the Río Bermejo, Argentina, a lowland river running ∼1, 270 km without tributaries. Weekly POC concentration and isotopic composition from 2016 to 2018 show that during the wet season, increased lateral channel migration generates an influx of 13 C‐enriched and 14 C‐enriched floodplain‐sourced material, overprinting the 13 C‐depleted and 14 C‐depleted headwater signature that is observed during the dry season. These findings demonstrate how channel morphodynamics can drive variability of POC composition in lowland rivers, and may modulate the composition of POC preserved in sedimentary archives. Plain Language Summary: Reconstruction of past climate conditions is often based on the chemistry of organic matter transported from rivers into ocean basins. However, it is unclear how organic matter chemistry changes from its original continental source to its final sink in ocean basins. As organic matter moves downstream through lowland rivers, this material can be deposited in floodplains. During floodplain storage, organic matter is decomposed and replaced, changing its chemistry and, ultimately the record of past climate. To understand how organic matter chemistry changes seasonally, we collected weekly samples of suspended sediment in the Río Bermejo, Argentina for two consecutive years. We measured changes in organic matter chemistry and in the rate of river bank erosion. We found that the Río Bermejo transports more organic matter sourced from mountains at periods of low flow, when the river does not erode its banks, and the river transports more organic matter sourced from floodplains during periods of high flow, when the river actively migrates. Because high flow periods account for most of the annual organic matter export, our results suggest that river‐sourced organic matter in ocean basins is likely a mix of soil, sediment, and vegetation from floodplains. Key Points: Discharge and river lateral migration rate set particulate organic carbon (POC) isotopic composition in a lowland river High lateral channel migration rates during the wet season drive replacement of headwater‐sourced POC by floodplain POC Wet seasons account for ∼85% of the annual POC export, suggesting that POC export is dominated by floodplain‐sourced organic matter